Design and Performance of Scaled-Up Microwave Dryer for Seaweed Drying - Arif Rahman Hakim; Wahyu Tri Handoyo; Adrianto Widi Prasetya (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2020)
Direct sunlight is commonly used to dry fresh seaweed by artisanal farmers in Indonesia due to its low cost and ease of handling. Nevertheless, this method poses some drawbacks such as lengthy duration, weather dependency and quality degradation. The application of microwave technology in food processing has progressed dramatically, including in the drying process. The microwave drying method is more efficient and can shorten the processing time. This study aimed to describe a large-scale microwave dryer (MD) design and performance to assist the fresh seaweed drying process. The design concept applies microwave energy with a volumetric heating feature to accelerate the seaweed drying process without damaging its functional groups. The MD dimensions were 2410 (l) x 270 (w) x 210 (h) mm with a dryer capacity of up to six kilograms, an enlarged cavity and multiple magnetrons. The main components of the MD were cavity, air circulation system, drying system and control system. According to the performance testing, the MD’s optimum performance was at a power level setting of P7 and six kilograms load. At this setting, we obtained a dried seaweed with a moisture ratio of 0.68±0.05, drying rate of 30.29±1.32 g/min, specific energy consumption of 3.96±0.08 MJ/kg H2O and energy efficiency of 58.45±2.65%. The total power of the P7 setting operation required 2.00 kW. Fourier-Transform Infrared (FTIR) spectra showed that the functional groups of the dried seaweed were unaltered.